2022
DOI: 10.1093/mnras/stac3446
|View full text |Cite
|
Sign up to set email alerts
|

The FRB 20121102A November rain in 2018 observed with the Arecibo Telescope

Abstract: We present 849 new bursts from FRB 20121102A detected with the 305-m Arecibo Telescope. Observations were conducted as part of our regular campaign to monitor activity and evolution of burst properties. The 10 reported observations were carried out between 1150 and 1730MHz and fall in the active period around November 2018. All bursts were dedispersed at the same dispersion measure and are consistent with a single value of (562.4±0.1)pc cm−3. The rate varies between 0 bursts and 218(16) bursts per hour, the hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 87 publications
2
20
0
Order By: Relevance
“…For a relatively small sample of FRB 20121102, it has been found that the waiting times deviate from the Poisson distribution (Wang & Yu 2017;Oppermann et al 2018;Wadiasingh & Timokhin 2019;Cheng et al 2020). The waiting times have been found to follow a bimodal distribution with peaks at milliseconds and tens of seconds from the large samples of FRB 20121102 (Li et al 2021;Hewittet al 2022;Jahns et al 2023) and FRB 20201124A (Xu et al 2022). It is possible that the short waiting time is only the substructure of longer bursts.…”
Section: Introductionmentioning
confidence: 99%
“…For a relatively small sample of FRB 20121102, it has been found that the waiting times deviate from the Poisson distribution (Wang & Yu 2017;Oppermann et al 2018;Wadiasingh & Timokhin 2019;Cheng et al 2020). The waiting times have been found to follow a bimodal distribution with peaks at milliseconds and tens of seconds from the large samples of FRB 20121102 (Li et al 2021;Hewittet al 2022;Jahns et al 2023) and FRB 20201124A (Xu et al 2022). It is possible that the short waiting time is only the substructure of longer bursts.…”
Section: Introductionmentioning
confidence: 99%
“…20 https://www.chime-frb.ca/ 21 Typical ZTF and ATLAS PSF FWHMs are 2″ and 4″, respectively, comparable to and larger than the adopted FRB localization error limit. 22 o Data sources: Arecibo (Spitler et al 2014;Scholz et al 2016;Spitler et al 2016;Scholz et al 2017;MAGIC Collaboration et al 2018;Michilli et al 2018;Gourdji et al 2019;Hessels et al 2019;Aggarwal et al 2021;Hewitt et al 2022;Jahns et al 2023), Apertif (Oostrum et al 2017(Oostrum et al , 2020, CHIME (Josephy et al 2019), DSN (Majid et al 2020;Pearlman et al 2020), Effelsberg (Hardy et al 2017;Spitler et al 2018;Houben et al 2019;Cruces et al 2021;, EVN (Marcote et al 2017), FAST , GBT (Scholz et al 2016(Scholz et al , 2017Gajjar et al 2018;Michilli et al 2018;Zhang et al 2018;Hessels et al 2019) u Mean distance of a wide range estimated with various techniques (∼4.4-14.2 kpc; e.g., Park et al 2013;Pavlović et al 2013Pavlović et al , 2014Surnis et al 2016;Kothes et al 2018;Mereghetti et al 2020;Zhou et al 2020). (This table is available in machine-readable form.…”
Section: Optical Observationsmentioning
confidence: 99%
“…Second, the high sensitivity of FAST can resolve more sub-bursts. However, the definition of sub-bursts is ambiguity at present (Li et al 2021;Jahns et al 2023;Xu et al 2022). It has been found that the short waiting times of FRBs are contaminated by sub-bursts (Jahns et al 2023).…”
Section: Waiting Time Distributions For Repeating Frbsmentioning
confidence: 99%
“…However, the definition of sub-bursts is ambiguity at present (Li et al 2021;Jahns et al 2023;Xu et al 2022). It has been found that the short waiting times of FRBs are contaminated by sub-bursts (Jahns et al 2023). From the above analysis, we have found that the short waiting times cannot be fitted by the Poisson model and the non-stationary Poisson model.…”
Section: Waiting Time Distributions For Repeating Frbsmentioning
confidence: 99%
See 1 more Smart Citation